2002
DOI: 10.4141/a02-017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary particle size and nutrient supply on energy digestibility and nitrogen excretion in ileal cannulated grower pigs

Abstract: Oryschak, M. A. and Zijlstra, R. T. 2002. Effect of dietary particle size and nutrient supply on energy digestibility and nitrogen excretion in ileal cannulated grower pigs. Can J. Anim Sci. 82: 603-606. Diets with two particle sizes (600 and 900 µm) and two nutrient supply levels [digestible energy (DE)-limiting and amino acid (AA)-limiting; 2.8 and 1.8 g digestible lysine Mcal -1 DE, , respectively] were used. Eight ileal cannulated pigs (25 ± 2 kg) had restricted access to feed (3 × maintenance DE) for thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
1
1
0
1
Order By: Relevance
“…It is well‐known that a reduction in particle size of feed ingredient will improve the digestibility of dietary nutrients, and subsequently reduce N and P excretion. In this study, reducing the particle size of brown rice from 800 to 600 μm for young pigs significantly decreased the fecal N excretion, which was similar with Oryschak and Zijlstra (), who reported that a reduction in particle size from 850 to 400 μm reduced fecal N excretion 18%. However, the reducing particle size in brown rice had no effect on P balance, which was consistent with observations by Rojas and Stein () who reported that a reduction in particle size did not affect the ATTD of P in corn.…”
Section: Discussionsupporting
confidence: 90%
“…It is well‐known that a reduction in particle size of feed ingredient will improve the digestibility of dietary nutrients, and subsequently reduce N and P excretion. In this study, reducing the particle size of brown rice from 800 to 600 μm for young pigs significantly decreased the fecal N excretion, which was similar with Oryschak and Zijlstra (), who reported that a reduction in particle size from 850 to 400 μm reduced fecal N excretion 18%. However, the reducing particle size in brown rice had no effect on P balance, which was consistent with observations by Rojas and Stein () who reported that a reduction in particle size did not affect the ATTD of P in corn.…”
Section: Discussionsupporting
confidence: 90%
“…A digestibilidade dos grãos finos afeta a excreção de nitrogênio (N) e fósforo (P) pelos suínos. Oryschak et al (2002) notaram que há poucos estudos sobre o efeito da redução do tamanho dos grãos sobre a digestibilidade e a excreção de N e P, combinada com a suplementação enzimática. Assim, os autores avaliaram os efeitos do tamanho dos grãos de cevada e ervilha (DGM's de 400 e 700 µm) na dieta de suínos em crescimento sobre a taxa de excreção de N e P. Foi constatado que o tamanho dos grãos afetou a excreção de P nas fezes, mas não na urina e, além disto, a redução do tamanho dos grãos (400µm) diminuiu em 12% a excreção de P nas fezes e, portanto, aumentou em 15% sua digestibilidade e retenção.…”
Section: Efeitos Da Granulometria Sobre O Desempenho E a Saúde Dos Suínosunclassified
“…Cereal grains are milled before being incorporated into pig diets, and different milling protocols will result in diets of different average particle size and particle size distribution. Particle size has been reported to influence nutrient digestibility, growth rate, feed intake, feed conversion ratio and gut health, especially in terms of gastric ulceration (Healy et al, 1994;Wondra et al, 1995a, b, c, d, e;Mavromichalis et al, 2000;Kim et al, 2002;Oryschak and Zijlstra, 2002;Lawrence et al, 2003;Choct et al, 2004). In New Zealand, barley is the main cereal grain used in pig diet.…”
Section: Introductionmentioning
confidence: 99%